Opportunities to Implement Mutual Legal Assistance in Criminal Law Enforcement in Indonesia - Kurniawan, Itok Dwi; Setyawan, Vincentius (Universitas Muhammadiyah Bima, 2022)
Studies on Mutual Legal Assistance (MLA) in various countries around the world have been carried out. However, for Indonesia, this is a new thing. So this article aims to examine Mutual Legal Assistance from the perspective of law and social contracts. This study explores methods for obtaining witness statements of foreign nationals. The writing of this article uses a normative legal research method, with a conceptual and statutory approach. The technique of analyzing legal materials used in writing this article is literature study. The results of this study are that it can be seen that foreign nationals have the right to refuse to give their statements before an Indonesian court, and there are no legal consequences whatsoever. Based on this phenomenon, it causes a lack of evidence that is very important in the examination of criminal cases, namely witness statements.